2017
DOI: 10.1515/ijamh-2017-0046
|View full text |Cite
|
Sign up to set email alerts
|

The theoretical underpinnings of Internet addiction and its association with psychopathology in adolescence

Abstract: This paper reviews the psychological and theoretical underpinnings that might help to explain the reported relationship between Internet addiction (IA) and psychopathology in both children and adolescents. Drawing on cognitive-behavioural models and social-skills theory, IA shows a strong relationship with depression, attention deficit hyperactivity disorder (ADHD) and time spent using the Internet use. Mixed findings are reported for social anxiety. Loneliness and hostility were also found to be associated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 36 publications
1
10
0
Order By: Relevance
“…Summarizing, according to Taylor et al, 39 who make use of cognitive-behavioral models and social-skills theory, there is a strong relationship between depression and time spent using the Internet, whereas more mixed findings are reported for social anxiety. Loneliness and hostility were also found to correlate with Internet use.…”
Section: Discussionmentioning
confidence: 99%
“…Summarizing, according to Taylor et al, 39 who make use of cognitive-behavioral models and social-skills theory, there is a strong relationship between depression and time spent using the Internet, whereas more mixed findings are reported for social anxiety. Loneliness and hostility were also found to correlate with Internet use.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, most prior studies have treated social anxiety, depression, and loneliness as risk factors for Internet-relevant addiction (8, 9), whereas, few studies have examined the alternative direction (10). A relevant study found that the relative risk for depression in students with Internet addiction after months was 1.5 times higher than that of non-Internet addiction participants, after controlling for potential confounding variables (gender, study burden, age, rural, or urban school).…”
Section: Introductionmentioning
confidence: 99%
“…Internet use has become an indispensable part of modern life, and, as a result, problematic internet use (PIU) is becoming a public health concern. In particular, excessive internet use at a young age is known to cause psychological, physical, and behavioral problems, such as attention disorder, cognitive impairment, and obesity related to a lack of physical activity [ 1 , 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%